Middlebury College 2013-14 John Hamilton Fulton Lecture in the Liberal Arts: a public conversation with Angelique Kidjo - Kafumbe, Damascus (International Library of African Music, 2014)
On October 2 and 3, 2013 Middlebury College hosted Grammy Award-winning artist and social advocate Angelique Kidjo to give the 2013—14 John Hamilton Fulton Memorial Lecture in the Liberal Arts and to perform a concert.
Keywords: African Music